Adoption of hybrid maize in Zambia: effects on gender roles, food consumption, and nutrition - Kumar, Shubh K. (International Food Policy Research Institute, 1994)
In this report, Shubh K. Kumar examines the reasons for low productivity of maize, the principal crop in Eastern Province, Zambia, compared with its potential, and suggests steps for increasing future productivity. The report also looks at the effects of adoption of hybrid maize on household consumption, nutrition, health, income, and labor and on how these may be redistributed within the household as a result of adoption. In particular, it focuses on changes in women's roles in crop management and resulting changes in allocation of time and money. The report is based on a collaborative study in Eastern Province conducted in 1986 by the International Food Policy Research Institute with the University of Zambia's Rural Development Studies Bureau and the Zambian National Food and Nutrition Commission to examine the growth and equity effects of technological change.